Influence of storm timing and forward speed on tides and storm surge during Hurricane Matthew. (May 2019) - Thomas, Ajimon; Dietrich, JC; Asher, TG; Bell, M; Blanton, BO; Copeland, JH; Cox, AT; Dawson, CN; Fleming, JG; Luettich, RA
Abstract: The amount and extent of coastal flooding caused by hurricanes can be sensitive to the timing or speed of the storm. For storms moving parallel to the coast, the hazards can be stretched over a larger area. Hurricane Matthew was a powerful storm that impacted the southeastern U.S. during October 2016, moving mostly parallel to the coastline from Florida through North Carolina. In this study, three sources for atmospheric forcing are considered for a simulation of Matthew's water levels, which are validated against extensive observations, and then the storm's effects are explored on this long coastline. It is hypothesized that the spatial variability of Matthew's effects on total water levels is partly due to the surge interacting nonlinearly with tides. By changing the time of occurrence of the storm, differences in storm surge are observed in different regions due to the storm coinciding with other periods in the tidal cycles. These differences are found to be as large as 1 m and comparable to the tidal amplitude. A change in forward speed of the storm also should alter its associated flooding due to differences in the duration over which the storm impacts the coastal waters. With respect to the forward speed, the present study contributes to established results by considering the scenario of a shore-parallel hurricane. A faster storm caused an increase in peak water levels along the coast but a decrease in the overall volume of inundation. On the other hand, a slower storm pushed more water into the estuaries and bays and flooded a larger section of the coast. Implications for short-term forecasting and long-term design studies for storms moving parallel to long coastlines are discussed herein. Highlights: OWI winds represent Hurricane Matthew's effects more accurately than WF and GAHM. Nonlinear interaction between surge and tide can alter storm tide significantly. A shore-parallel storm can interact with various stages in the tidal cycle. A faster storm would have caused higher surges on the open coast. A slower storm would have pushed more water into the estuaries and bays.